If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ((10x + -1) + -1(5x + 1)) = 61 Reorder the terms: ((-1 + 10x) + -1(5x + 1)) = 61 Remove parenthesis around (-1 + 10x) (-1 + 10x + -1(5x + 1)) = 61 Reorder the terms: (-1 + 10x + -1(1 + 5x)) = 61 (-1 + 10x + (1 * -1 + 5x * -1)) = 61 (-1 + 10x + (-1 + -5x)) = 61 Reorder the terms: (-1 + -1 + 10x + -5x) = 61 Combine like terms: -1 + -1 = -2 (-2 + 10x + -5x) = 61 Combine like terms: 10x + -5x = 5x (-2 + 5x) = 61 Remove parenthesis around (-2 + 5x) -2 + 5x = 61 Solving -2 + 5x = 61 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 5x = 61 + 2 Combine like terms: -2 + 2 = 0 0 + 5x = 61 + 2 5x = 61 + 2 Combine like terms: 61 + 2 = 63 5x = 63 Divide each side by '5'. x = 12.6 Simplifying x = 12.6
| 25+30/(2-1) | | 3x/20+5x/7-1/14 | | 6(1-4b)=-114 | | -6x+10=153+7x | | 4y^4-101y^2+25=0 | | 19+(-2)= | | 25+(30/2-1) | | 4h+-1=4h+7 | | 2+4(4n-3)=-5(6n+8)-8n | | 2x-12+6=4x-2 | | 80-x=3(90-x)+10 | | -11=-4(4+2m) | | 30+5b=-5(b-4) | | -38-4a=2(5-5a) | | -31=9-6p-7p | | 3=-2*1+b | | 324=-6(7x-5) | | -8=6g+3 | | -2(x+3x)=4x-3 | | -11=-4(4+2) | | 23/6/38/6 | | h=-16t^2+100+30 | | (x+9)(x+5)=(x+1)(x+1) | | 6x+4x-2=-22 | | z^2/6-3z/2-27=0 | | 5x+-2=9x+4 | | -4x-64=26-9x | | x/3+(x+1)/2=x | | (y-8)/5=(y+3)/2 | | 23/638/6 | | 45=3a+9-2a | | 88=4(8-2a) |